Handicapped children: Emotional development and role of the therapist - R. S. Jacobson; G. Straker (AOSIS, 1979)
The development of trust, pride and autonomy, initiative and industry in the first ten years of childhood is described. The problems encountered by the handicapped child and his parents are pointed out. The role the therapist can play and the self knowledge necessary for this role are briefly discussed.